Ecosophy as a form of protection for the Tapanuli Orangutan (Pongo tapanuliensis) in the Batang Toru Landscape, North Sumatra, Indonesia - YUDHA LESMANA; SAMBAS BASUNI; RINEKSO SOEKMADI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Lesmana Y, Basuni S, Soekmadi R. 2024. Ecosophy as a form of protection for the Tapanuli Orangutan (Pongo tapanuliensis) in the Batang Toru Landscape, North Sumatra, Indonesia. Biodiversitas 25: 4535-4542. Forest clearing for economic development often conflicts with saving biodiversity. Forest clearing by humans to date has been anthropocentric in its utilization of forest resources, which are still classified as exploitative in the Batang Toru Landscape, South Tapanuli District, North Sumatra, Indonesia. As a result, the Tapanuli orangutan (Pongo tapanuliensis) become alienated in its own home and migrates to community gardens for get food. The community considers orangutans to be very cruel by stealing and destroying their plantation products, which results in a decrease in economic income, triggering human-orangutan conflict. Local communities carry out evictions in various ways based on their initiatives and experiences. This study aims to analyze the concept of ecosophy (ecological philosophy)and factors of human-orangutan conflict as an alternative conservation of wild and endangered species protection. The research location focused on six sub-districts of the Tapanuli orangutan range in the other-use forest area of South Tapanuli District. This research used qualitative methods through interviews and discussions with communities living around the forest. The results showed that the concept of ecosophy can integrate intellectual, spiritual, and emotional dimensions at all levels of education for public awareness of the importance of protecting the Tapanuli orangutan. Higher levels of education showed positive results towards saving the Tapanuli orangutan. This study suggests that a long-term solution to human-orangutan conflict requires a comprehensive approach that emphasizes the ecosophy between humans and nature.